MEMAHAMI PARADIGMA PENDIDIKAN SENI - Alfa Kristanto (Sekolah Tinggi Theologia Abdiel, 2017)
Understanding the paradigm of art education can help in understanding the essence of art education. Diversity paradigm can make the difference of interest in understanding the art of holistic education. Faced with the fact of diversity in the understanding of art education it is important to understand the paradigm of arts education together. Starting two views on arts education is education in the arts and education through art that led to the understanding of the general paradigm that continues to be able to understand art education.